Comparison between capnodynamic and thermodilution method for cardiac output monitoring during major abdominal surgery: An observational study. Issue 12 (December 2021) - Sigmundsson, Thorir S.; Öhman, Tomas; Hallbäck, Magnus; Suarez-Sipmann, Fernando; Wallin, Mats; Oldner, Anders; Hällsjö-Sander, Caroline; Björne, Håkan
Abstract : BACKGROUND: Cardiac output ( CO ) monitoring is the basis of goal-directed treatment for major abdominal surgery. A capnodynamic method estimating cardiac output ( CO EPBF ) by continuously calculating nonshunted pulmonary blood flow has previously shown good agreement and trending ability when evaluated in mechanically ventilated pigs. OBJECTIVES: To compare the performance of the capnodynamic method of CO monitoring with transpulmonary thermodilution ( CO TPTD ) in patients undergoing major abdominal surgery. DESIGN: Prospective, observational, method comparison study. Simultaneous measurements of CO EPBF and CO TPTD were performed before incision at baseline and before and after increased (+10 cmH2 O) positive end-expiratory pressure (PEEP), activation of epidural anaesthesia and intra-operative events of hypovolemia and low CO . The first 25 patients were ventilated with PEEP 5 cmH2 O (PEEP5 ), while in the last 10 patients, lung recruitment followed by individual PEEP adjustment (PEEPadj ) was performed before protocol start. SETTING: Karolinska University Hospital, Stockholm, Sweden. PATIENTS: In total, 35 patients (>18 years) scheduled for major abdominal surgery with advanced hemodynamic monitoring were included in the study. MAIN OUTCOME MEASURES AND ANALYSIS: Agreement and trending ability between CO EPBF and CO TPTD at different clinical moments were analysed with Bland--Altman and four quadrant plots. RESULTS: In total, 322 paired values, 227 in PEEP5 and 95 in PEEPadj were analysed. Respectively, the mean CO EPBF and CO TPTD were 4.5 ± 1.0 and 4.8 ± 1.1 in the PEEP5 group and 4.9 ± 1.2 and 5.0 ± 1.0 l min −1 in the PEEPadj group. Mean bias (levels of agreement) and percentage error (PE) were −0.2 (−2.2 to 1.7) l min −1 and 41% for the PEEP5 group and −0.1 (−1.7 to 1.5) l min −1 and 31% in the PEEPadj group. Concordance rates during changes in CO EPBF and CO TPTD were 92% in the PEEP5 group and 90% in the PEEPadj group. CONCLUSION: CO EPBF provides continuous noninvasive CO estimation with acceptable performance, which improved after lung recruitment and PEEP adjustment, although not interchangeable with C OTPTD . This method may become a tool for continuous intra-operative CO monitoring during general anaesthesia in the future. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT03444545. Abstract : Supplemental Digital Content is available in the text